Determination of pressure gradient in mitral stenosis with Doppler echocardiography. - Holen, J (1979)
The accuracy of a non-invasive ultrasound Doppler technique for the determination of the pressure gradient in mitral stenosis was evaluated in a study of 8 adult patients. Transseptal left atrial catheterisation and retrograde left ventricular catheterisation were performed. The same diastoles were used to compare the gradient constructed from the ultrasound data (delta PU) with that constructed from the manometric data (delta PM). In the 8 patients the difference betweent he mean diastolic values of delta PU and delta PM was - 0.54 +/- 1.0 (SD) mmHg. The corresponding figure for mid-diastole was 0.01 +/- 0.9 (SD) mmHg. The results indicate that the ultrasound technique is sufficiently accurate for diagnostic purposes.